Radat Ya Allah Ya Tuhan Kami Dance Revitalization in the Tempatan Village - Taslima, Tata; Oktariani, Dwi; Ismunandar, Isminandar (Universitas Tanjungpura, 2024)
The background of this research is the loss of the art of the Radat Ya Allah Ya Tuhan Kami dance in the Tempatan village. This study aims to revive the Radat Ya Allah Ya Tuhan Kami Dance so that it can be widely recognized by the public and can be preserved again. This study uses descriptive methods, qualitative research forms and choreographic approaches. The data in this study are the results of interviews, observation results and documentation results. The data sources in this study were informants who knew about the Radat Ya Allah Ya Tuhan Kami Dance. Data collection techniques in this study are observation, interviews and documentation. The data collection tool in this study was the researcher as the first instrument, observation guidelines and interview guidelines. The data validation technique used is source triangulation and observation extension. Data analysis techniques in this study are analysis during data collection and analysis after data collection. The results of this study are to describe the process and results of the revitalization of the Radat Ya Allah Ya Tuhan Kami Dance, namely meeting with speakers, conducting dance training for new dancers and musicians, dissecting the form of dance performances, and re-performing the Radat Ya Allah Ya Tuhan Kami Dance in full using music. accompaniment, make-up and fashion.